2017
DOI: 10.23960/jipt.v5i1.p1-7
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Perendaman Telur Menggunakan Larutan Daun Kelor Terhadap Kualitas Internal Telur Ayam Ras

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
1
21

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 0 publications
3
8
1
21
Order By: Relevance
“…The decreasing viscosity of albumen causes a lower value of HU. This is as reported by Riawan et al (2017) that the decrease in egg white viscosity was mainly due to changes in gel structure and physicochemical damage of ovomucin fibers, which in turn can reduce HU. There was a significant reduction in HU from 0 to 14 d, which was almost 31%.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…The decreasing viscosity of albumen causes a lower value of HU. This is as reported by Riawan et al (2017) that the decrease in egg white viscosity was mainly due to changes in gel structure and physicochemical damage of ovomucin fibers, which in turn can reduce HU. There was a significant reduction in HU from 0 to 14 d, which was almost 31%.…”
Section: Resultssupporting
confidence: 75%
“…This is as stated by Azizah et al (2018) that ovomucin consists of α-ovomucin and β-ovomucin, where βovomucin is the most influential on albumen dilution. In line with this, Riawan et al (2017) and Saraswati (2015) also reported that the longer the storage, then the higher the decrease of thick albumen and finally the AI becomes lower. Overall, the average AI of duck eggs stored up to 14 d is still good, which is around 0.05-013.…”
Section: Resultssupporting
confidence: 54%
“…Penanganan telur bermanfaat untuk mempertahankan kualitas telur, sehingga telur dapat dikonsumsi dalam waktu yang lebih panjang. Penanganan telur yang biasa dilakukan diantaranya adalah dengan metode pembersihan telur segera setelah telur dikoleksi, pengemasan kering untuk memperlambat hilangnya air dan CO2, perendaman telur (Sulistina et al, 2013), pencelupan telur ke dalam berbagai jenis larutan (wulandari, et al 2013(wulandari, et al dan Tindjabate, et al, 2014, penutupan pori-pori telur dengan penyamak nabati (Riawan, et al 2017), dan yang paling mudah dan praktis untuk dilakukan oleh masyarakat umum yaitu penyimpanan dingin.…”
Section: Gambar 1 Penilaian Kualitas Telur Melalui Media Airunclassified
“…Penggunaan gel lidah buaya telah diaplikasikan di industri pangan sebagai ingridien pangan fungsional, dan salah satunya dengan menjadikan gel lidah buaya sebagai bahan untuk membentuk edible coating alami dan dapat menahan laju respirasi (Valverde et al, 2005). penyimpanan, peningkatan pH akibat penguapan CO2 dan kerusakan serabut ovomucin (Riawan et al, 2017).…”
Section: Pendahuluanunclassified